57 INHIBITION OF LEPTIN SIGNALING AMELIORATES UREMIC BONE DISEASE IN MICE. Issue 1 (1st January 2007) - Vanek, C.; Cheung, W.; Larson, E.; Klein, R.; Mak, R.
Abstract : Bone disease and fragility fractures are a common complication of renal insufficiency. Leptin levels are elevated in renal insufficiency. Leptin signaling, via the hypothalamic melanocortin system, regulates bone formation in rodents. Using transgenic mouse models, we examined the impact of central leptin signaling on femoral bone mass, size, and strength in uremia. Wild-type (WT), leptin-deficient (ob/ob), leptin receptor-deficient (db/db), and melanocortin receptor 4 knockout (MCR4-KO) mice underwent sham operation (S) or subtotal nephrectomy (Nx) at 8 weeks of age. Additional nephrectomized WT mice received intracerebroventricular infusions of agouti-related peptide (AGRP, 2 nmol) or vehicle. All mice were pair-fed and examined at 14 weeks. Femoral bone mineral density (BMD) and cortical cross-sectional area were determined by dual energy x-ray absorptiometry and x-ray microtomographic scanning. Femoral bone strength was assessed by three-point bending until failure. Blood urea nitrogen increased an average of 110% in all Nx mice groups. WT-Nx mice had significant decreases in femoral BMD, cortical area, and failure load compared with sham-operated controls, whereas the skeletal integrity of mouse strains with impaired leptin signaling (ob/ob, db/db, and MCR4-KO) was unaffected by the uremic state. Treatment of WT mice with AGRP, a melanocortin receptor antagonist, prevented the declines in femoral mass, size, and strength that accompany Nx. These findings suggest that inhibition of central leptin signaling pathways may be of benefit in offsetting the adverse consequences of renal failure on the skeleton.